Research on performance degradation of force sensors based on improved error back propagation algorithm - Wang, Pengling; Wang, Peng; Wang, Chu; Wang, Bin; Chen, Chen; Li, Liangliang (Journal of physics. Conference series, 2024)
Studying the performance degradation of force sensors, a core component of aircraft control stick force measurement devices, is essential. The key to investigating equipment performance degradation lies in constructing a degradation model. When dealing with degradation data from specific devices, relying solely on fitting methods may not effectively describe the degradation of the equipment. This study introduces an error backpropagation neural network model for constructing the performance degradation model of force sensors, and optimization improvements are made by using a genetic algorithm. Experimental results demonstrate a 99% reduction in Root Mean Square Error with the proposed modeling approach.